Conservative treatment of isolated medial orbital wall fractures - ŞAHİN, ÖZLEM (SLACK INC, 2006)
The decision to use surgical or nonsurgical treatment for orbital blow-out fractures is still controversial. Previously, it was advocated that all blow-out fractures should be treated surgically based on the conception that extraocular muscles were blown out and trapped in the fracture area. However, a shift to a more conservative approach occurred gradually, most likely due to the evidence of spontaneous improvement. The medical records of two patients who were diagnosed as having an isolated medial wall fracture with medial rectus muscle displacement into the ethmoid sinus, as demonstrated by computed tomography, were reviewed. Both patients showed improvement only with conservative therapy.
Keywords: BLOW-OUT FRACTURES; MANAGEMENT; FLOOR; REPAIR; ENTRAPMENT